PENERAPAN E-GOVERNMENT DALAM MENINGKATKAN AKUNTABILITAS PENGELOLAAN DANA DESA DI DESA KALEMPANG KABUPATEN SIDENRENG RAPPANG - Aman Darmawan; Herman Dema; Muhammad Rais Rahmat Razak; Sandi Lubis (LPPM Universitas Abdurrab, 2025)
This study aims to examine the implementation of e-government through the Village Financial System application (SISKEUDES) in enhancing the accountability of village fund management in Kalempang Village, Pitu Riawa Subdistrict, Sidenreng Rappang Regency. Employing a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation involving village officials, BPD members, and community representatives. The data were analyzed using Miles and Huberman’s interactive model, focusing on three dimensions: digitalization elements (support, capacity, value), accountability indicators (commitment, guarantee, report, result, morality), and implementation barriers. The findings indicate that SISKEUDES contributes positively to administrative efficiency and internal control but falls short in promoting public transparency and participation. The most prominent digitalization element is value, while guarantee stands out among accountability indicators. Major obstacles include limited infrastructure, low digital literacy among officials, and minimal public access to financial information. This study highlights the importance of integrating digital systems with local institutional structures to foster inclusive, transparent, and participatory village governance. Practical recommendations include regular training, infrastructure enhancement, and the development of publicly accessible budget dashboards Keywords : E-Government, Village Fund Management, Accountability, Siskeudes, Digital Governance